The Influence of the U.S. Economy on the Financial Businesses Act and Fluctuation of Thai Economy - Charnvitayapong, Kovit; Dangpradub, Thitaya (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The purpose of this study is to examine whether the financial rules and regulations, economic policies, and international agreements of the U.S. could be the source of banking, financial business laws, and economic fluctuations in small-opened economies, one of which is Thailand. This study used documentary research and inductive reasoning to examine the origins of the U.S. Great Depression in 1929 and the other three global economic crises: the Latin, Asian, and subprime crises. The findings seemed to support the notion that U.S. financial laws, rules, regulations, economic policies, economic problems, international agreements, and policy remedies may cause economic fluctuations in countries with small-opened economies. To avoid these economic fluctuations, small-open-economy countries should defend themselves when signing international agreements. They should make use of reservation clauses in the international agreement. The final proposal is that small-open economies, such as Asian countries, should form an institution with the same function as the IMF to maintain the group's financial stability.